Numerical study of a turbulent hydrogen flame in oxy-combustion regimes - Wawrzak, A.; Tyliszczak, A. (Archives of Mechanics, 2017)
This paper presents the results of large eddy simulation/conditional moment closure (LES-CMC) computations of a turbulent flame in oxy-combustion regimes complemented by 0D-CMC analysis. The fuel is pure hydrogen and it issues into a hot oxidiser stream which is a mixture of oxygen and water vapour. The flame is initiated by a spark, then it spreads and propagates through the domain and eventually stabilises as a lifted or attached one. The present problem offers new challenges to combustion modelling as the observed combustion process is strongly unsteady. In cases of large content of oxygen in the oxidiser stream the flame has very high temperature (≈ 3000 K) and large temperature/density variations. Nevertheless, it is shown that LES-CMC simulations are stable in such conditions and can be successfully applied to oxy-combustion studies. We analyse the dependence of the flame temperatures and lift-off height of the flames LH on the oxidiser composition and chemical kinetics. It is shown that both these factors may affect the flame behaviour. We identified the conditions in which LH exhibits a linear dependence on the oxidiser composition independently of applied chemical kinetics, and the regimes where the LH changes in a non-linear manner and strongly depends on the chemical kinetics.